(3JJeI GdEHGfIs - (3YHO GdQMef Hf eCehf GdfjSGHhQqi, CHh SYO, GdeYQha HGdoenJnhpqdj , (B478 (3g` s; (3GdahQGfj , YHO GdQMef Hf eMeO Hf CMeO Hf ahQGf, CHh GdbGSe,J (B461 (3g` s
(3ChdgG (B:s
(3GdHGH GdSGOS YTQ ai bSeI GdUObGJ s
(3BNQgG (B:s
(3Ef GdPHM jNJU HCjGe GdJTQjb hGddg CYde fLR GdLRA GdKGdK ef JJeI GdEHGfI hGdMeO ddg hMOg jJdhg ai Chd GdQGHY cJGH GdHjY s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B169s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs